E-administracja w rozwoju usług edukacyjnych – szkoła jako organizacja „ucząca się” - Raszewska-Skałecka, Renata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
Education in the information society is the most important sphere of state activity, which supplies educated staff in the state’s public administration structure. School and the development of the educational process in society (information, knowledge, skills, predispositions and experience of staff) serve the development of the state and the common good.
Keywords: intelligent administration; education; information society